2014
DOI: 10.1177/1087054714561858
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the ADHD Phenotype Using the Strengths and Difficulties Questionnaire in a Clinical Sample of Newly Referred Children and Adolescents

Abstract: Our study supports the use of the SDQ in the screening for ADHD. However, not all ADHD subtypes are equally screened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
2
13
1
2
Order By: Relevance
“…The SDQ is available at no cost in multiple (>80) languages and has ability to screen for other problems. Potential drawbacks of the SDQ include lower sensitivity for the inattentive presentation of ADHD, 52,53 which is often more prevalent in epilepsy populations. 14,16,54 However, this weakness was not reflected in the studies reviewed here where the combined subtype was more prevalent, and thus may be contributing to the strong ability of the SDQ to perform well.…”
Section: What Screening Tools Should Be Used and How Should Adhd Bementioning
confidence: 99%
“…The SDQ is available at no cost in multiple (>80) languages and has ability to screen for other problems. Potential drawbacks of the SDQ include lower sensitivity for the inattentive presentation of ADHD, 52,53 which is often more prevalent in epilepsy populations. 14,16,54 However, this weakness was not reflected in the studies reviewed here where the combined subtype was more prevalent, and thus may be contributing to the strong ability of the SDQ to perform well.…”
Section: What Screening Tools Should Be Used and How Should Adhd Bementioning
confidence: 99%
“…Screening studies suggest a cut-off of 8/10 as providing the best ADHD diagnostic accuracy (Carballo et al, 2014). Using a cut-off of 8, we separated the HR ASD group into a HR/ASD-HI group (n=26), including children whose probands scored below 8 (average=5.19; SD=1.7) and a HR/ASD+HI group (n=20), when probands …”
Section: Assessing Hyperactivity/inattention-riskmentioning
confidence: 99%
“…7,8 The HI subscale consists of 5 items about hyperactivity-impulsivity and inattention, and has been put forward as a good screener for ADHD in schoolchildren, in both epidemiological 9 and clinical studies. 10,11 Psychometric SDQ studies in preschool children are still limited, but satisfactory internal consistencies for the parent and teacher SDQ HI subscales have been reported. [12][13][14][15][16][17][18] We identified 4 studies that included preschoolers and investigated the screening accuracy of the SDQ HI subscale for ADHD.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18] We identified 4 studies that included preschoolers and investigated the screening accuracy of the SDQ HI subscale for ADHD. 10,15,19,20 Two community studies (n ¼ 18,232, age range 5-15 years; n ¼ 1341, age 3 years) 15,20 concluded that the parent SDQ HI subscale discriminated well between children with and without ADHD. A longitudinal study (age range 5-7 years) found that HI subscale scores !6 and reported impact by parents and teachers gave about a 20-fold increased risk of subsequent ADHD.…”
mentioning
confidence: 99%
See 1 more Smart Citation